The Fulfillment of Political Rights for People with Disability in 2019 Concurrent Elections by General Election Commission of Yogyakarta City - Azka Abdi Amrurobbi; Bambang Eka Cahya Widodo; Moch Edward Trias Pahlevi; Salman Alfarisi (Soshum: Jurnal Sosial dan Humaniora, 2020)
The rights of PWDs especially political rights are still marginalized even though there are many regulations that guarantee equal rights for PWDs. This research used descriptive qualitative to be able to find out how the model of political access improvement for peoplewith disabilities by the Yogyakarta City General Election in the 2019 Concurrent Elections. The results showed that there are five steps in establishing a model of political access improvment for PWDs. First, the identification of problems faced by persons with disabilities is done by Focus Group Discussion. Second, conceptualization is done based on the identification of problems and produces several models. Third, the estimated parameters determined refer to KPU regulation No. 10 of 2018. Fourth, validation is done by simulating several models with the aim of whether the model is going well or not. Fifth, after passing through the four stages, the model of increasing political access for persons with disabilities can be applied.